A rare case of leiomyosarcoma of cervix and challenges in its management: a case report and brief review of literature - Mehra, Reeti; Sidhu, Sukhbir P.K.; Pandey, Awadhesh K.; Garg, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Leiomyosarcoma of cervix is an aggressive and rare tumour of the cervix with poor prognosis. Management plan differs greatly from other common cervical malignancies. A 38 year old multiparous lady presented with a large circumferential cervical tumour which was diagnosed as leiomyosarcoma of cervix on cervical biopsy. It was a surgical challenge. Patient underwent pre-operative ureteric stenting followed by exploratory laparotomy with hysterectomy with bilateral salphingo-oophorectomy. Surgical difficulties were encountered due to deep impaction of tumour in pelvis and altered anatomy due to the bulk of tumour. Retrograde approach was taken and pouch of Douglas was opened before clamping the mackenrodts and the uterus was bisected and debulking of tumour done simultaneously to facilitate the surgery. Post operatively patient received chemotherapy (Vincristine, adriamycin and cyclophosphamide) followed by radiotherapy. Patient developed vesicovaginal fistula and liver metastasis nine months post- surgery. She received second line of chemotherapy (gemcitabine and docetaxel) after which she was lost to follow up.